Vanadium Pentoxide Nanorods Anchored to and Wrapped with Graphene Nanosheets for High‐Power Asymmetric Supercapacitors. Issue 9 (18th August 2015) - Li, Ge; Wang, Xiaolei; Hassan, Fathy M.; Li, Matthew; Batmaz, Rasim; Xiao, Xingcheng; Yu, Aiping
Abstract The front cover artwork for Issue 09/2015 is provided by the group of Prof. Aiping Yu at the University of Waterloo (Canada). The image shows the design and development of V2O5 nanorods/graphene nanocomposites for high‐performance asymmetric supercapacitors. Read the full text of the Article at 10.1002/celc.201500057.